The Influence Of The Local Cultural Development Index On Indonesia's Economic Development (Panel Evidence From All Provinces In Indonesia) - Hermawan, Irfan; Suhendra, Indra; Sutjipto, Hady (UNIVED Press, 2026)
Economic growth is an economic issue and has become one of the important phenomena experienced by several developed and developing countries. High economic development is a target to be achieved, especially for developing countries. This study aims to identify the influence of the Cultural Development Index (CDI) in four dimensions: Cultural Economy (CEC), Cultural Heritage (CH), Cultural Expression (CEX), and Gender (GP) on the rate of economic growth (ERG). This study uses the Generalized Method of Moment (GMM) with data taken from secondary sources, namely the Central Statistics Agency (BPS), the Ministry of Women's Empowerment and Child Protection (KPPPA), the Ministry of Culture, and the Directorate General of Regional Development – Ministry of Home Affairs, using data from 32 provinces in Indonesia from 2018 to 2023. The estimation results using the GMM method show that the ratio of effectiveness in CEC results has a positive and significant effect, the ratio variable in CH has a positive and significant effect, The CEX ratio variable has a negative and significant effect, while the GP ratio variable has no significant effect.